Investigating the Effect Of Communication and Teamwork on Employee Performance: An Empirical Study in Indonesia Airport Company - Anggraini, Ayu Nadya; Ikut, Camilus Isidorus (Faculty of Economics and Business UNTAG Semarang, 2024)
The study aimed to investigate the effect of communication and teamwork on employee performance. The type of research used is a quantitative method, Primary data sources were obtained through a survey of all employees in the Operations and Services section of PT. Angkasa Pura 1, General Ahmad Yani International Airport Branch Office, Semarang, Central Java, Indonesia. The technique used a random sampling so a total of 52 employees were obtained. The results showed that communication had a positive effect on employee performance. Other finding concluded that teamwork had a positive and significant effect on employee performance. The results contribute to providing important evidence of building cooperation and communication in organizations.